OPTIMASI NAA DAN BAP TERHADAP PERTUMBUHAN DAN PERKEMBANGAN TUNAS MIKRO TANAMAN KANTONG SEMAR (Nepenthes mirabilis) SECARA IN VITRO - ROSMAINA ROSMAINA; DINNI ARYANI (Jurnal Agroteknologi, 2015)
Conventional propagation of Nepenthes was difficult to do. To overcome the problems were required alternative method such as in vitro propagation. The objective of this research was to obtain the best treatment of BAP + NAA on shoot multiplication of Nepenthes through in vitro culture. The research design used Randomized Completely Design consist of seven treatments, e.g. 1) ½ MS0 (control); 2) ½ MS + 1 ppm BAP + 0.5 ppm NAA; 3) ½ MS + 1 ppm BAP + 1 ppm NAA; 4) ½ MS + 1.5 ppm BAP + 0.5 ppm NAA; 5) ½ MS + 1.5 ppm BAP + 1 ppm NAA; 6) ½ MS + 2 ppm BAP + 0.5 ppm NAA dan 7) ½ MS + 2 ppm BAP + 1 ppm NAA. The parameter observed were number of shoot, number of nodul, number of leafs, number of pitcher and number of root. The result of this research showed that treatment of ½ MS + 1 ppm BAP + 1 ppm NAA is the best treatment compared to others. At induction stage, this treatment can produce the number of shoot, number of nodul, and number of root were 1.6 shoots/explant, 10.8 nodul/explant and 3.6 root/explant, respectively. At subculture, this treatment can produce the number of shoot, number of leafs, and number of pitcher were 5.8 shoots/explant, 12.4 leafs/explant and 5.2 pitcher/explant, respectively.